AGRIPRENEURSHIP AND WOMEN EMPOWERMENT IN CONFLICT-AFFECTED RURAL NIGERIA: DEVELOPMENT AND VALIDATION OF THE RURAL WOMEN AGRIPRENEURSHIP EMPOWERMENT INDEX (RWAEI) - Fidelis, Freda; Mercy Modupe, Adeyeye; Alabi, Jacob Abu (Applied Studies in Agribusiness and Commerce, 2025)
The Rural Women Agripreneurship Empowerment Index (RWAEI), a multifaceted instrument for assessing the empowerment results of agripreneurial engagement among rural women in Northeastern Nigerian regions affected by conflict, is introduced in this study. The study examines how access to mechanization, farm production, hired labor, and market engagement contribute to long-term economic inclusion, decision-making authority, and community leadership in addition to job creation. It is framed within Sen’s Capability Approach and Gendered Institutions Theory. The study uses confirmatory factor analysis (CFA), mediation analysis, and structural equation modeling (SEM) to validate the empowerment pathways and build the RWAEI model using data from 1,146 rural women in Gombe, Bauchi, and Adamawa. The findings show that the relationship between agripreneurship and empowerment is significantly mediated by labor employment and machine access.The index provides a context-specific metric for evaluating the agency and resilience of rural women, with a Cronbach’s alpha of 0.812. The results back up the combination of focused capacity-building initiatives and gender-sensitive agricultural policies to increase the effect of agribusiness. By shifting from output-based models to capability-focused empowerment assessment, the study advances the conversation around agripreneurship and has wide ranging implications for poverty alleviation, post-conflict recovery, and the implementation of the Sustainable Development Goals (SDGs).